Exploration of 21st century skills in students SMA Negeri 1 Sungai Tebelian - Nurfitrianti Sri; Indri Astuti; Afandi Afandi (Universitas Kanjuruhan Malang, 2023)
Educational planning is adjusted by considering the suitability of the education system in schools so that students are ready to enter the world of work with the skills needed so that they can be useful in the future. The aim of this research is to find out students' 21st-century skills. The method that the researchers used in this study were a quantitative descriptive research method, with indirect communication techniques, with a data collection tool in the form of a questionnaire. The questionnaires distributed amounted to 41 items and were analyzed using a Likert scale. The questions and sample of this research were 71 respondents who were class XII students of SMA Negeri 1 Sungai Tebelian. The results of this study showed a score of 80.34 so which could illustrate that the students of SMA Negeri 1 Sungai Tebelian had 21st-century skills in a good category